Mercury and Selenium in Subantarctic Commerson's dolphins (Cephalorhynchus c. commersonii). - Cáceres Saez, Iris (2012)
Total mercury (THg) and selenium (Se) concentrations were determined in hepatic, renal, and muscle tissues of seven specimens of Commerson´s dolphins incidentally captured in artisanal fisheries of Tierra del Fuego, Argentina, by instrumental neutron activation analysis. Liver yielded the mean highest concentration of THg 9.40 (9.92) μg g(-1) dry weight (DW) (standard deviation of the average in parenthesis); kidney and muscle showed similar values, ranging from 2.34 to 3.63 μg g(-1) DW. Selenium concentrations were similar in hepatic and renal tissues, with values from 13.62 to 14.56 μg g(-1) DW; the lowest concentration was observed in muscle, 4.13 (2.05) μg g(-1) DW. Among the specimens analyzed, the maximum concentrations of THg and Se were observed in the single adult female studied. An increasing age trend is observed for THg concentrations in tissues analyzed. The molar ratio of Se/Hg in the hepatic, renal, and muscle tissues were 8.7 (9.6), 13.2 (9.5), and 9.0 (11.4), respectively, suggesting Se protection against Hg toxicity. Silver concentrations in the three tissues were included, and the Se/(Hg + 0.5×Ag) molar ratio showed values closer to 1. Both Hg and Se concentrations in liver and kidney were comparable to those found in other small odontocetes from Argentine and Brazilian waters. This study constitutes the first joint description reported of Hg and Se concentrations in liver, kidney, and muscle of the Commerson´s dolphin species.